Combined gaze palsy of horizontal saccades and pursuit contralateral to a midbrain haemorrhage. - Bolling, J (1987)
A midbrain haemorrhage, revealed by CT, caused a contralateral supranuclear horizontal gaze palsy of both saccades and foveal pursuit. These findings confirm the hypothesis that the supranuclear pathways for pursuit decussate to the contralateral midbrain and then decussate back before innervating the ipsilateral paramedian pontine reticular formation.